Case Report: Anti-neutrophil Cytoplasmic Antibody-Associated Vasculitis With Acute Renal Failure and Pulmonary Hemorrhage May Occur After COVID-19 Vaccination - Chen, Chien-Chou; Chen, Hsin-Yang; Lu, Chun-Chi; Lin, Shih-Hua (Frontiers in Medicine, 2021)
The rare and severe adverse effects associated with COVID-19 vaccination have been under-appreciated, resulting in many instances of inappropriate management. We describe the case of an elderly woman who developed anti-neutrophil cytoplasmic antibody-associated vasculitis with pulmonary renal syndrome approximately 3 weeks after the first dose of COVID-19 mRNA vaccination (Moderna). Her nasopharyngeal polymerase chain reaction test for the COVID-19 RNA virus was negative. Gross hematuria, heavy proteinuria, acute renal failure (serum creatinine up to 6.5 mg/dL), and hemoptysis coupled with a marked increase in serum anti-myeloperoxidase-O antibody were observed. Renal biopsy showed severe vasculitis with pauci-immune crescent glomerulonephritis. The pulmonary hemorrhage was resolved and renal function improved following combined plasma exchange and the administration of systemic steroids and anti-CD20 therapy. The early examination of urinalysis and renal function may be crucial for identifying glomerulonephritis and acute renal failure in susceptible patients after COVID-19 vaccination.